Sentiment Analysis of Digital Sharia Banking - Abdullah Haidar; Aisyah As-Salafiyah; Evania Herindar (SMART Insight, 2022)
This study was conducted to review perceptions about digital Islamic banking within the scope of Islamic economics from a scientific perspective in published journals discussing the development of digital Islamic banking. The method used is descriptive statistical analysis with meta and sentiment analysis from secondary data in the form of 70 published papers in the last seven years which are then processed using Ms. Excel 2019 and SentiStrength. The results show that research on digital Islamic banking in the scientific literature has increased in quantity every year. The sentiment analysis results show that the differences of opinion among experts regarding digital Islamic banking tend to be varied, with the positive sentiment of 36%, then negative sentiment of 18%, and negative sentiment of 46%. This study is the first to discuss sentiment analysis on the theme of digital Islamic banking with secondary data with a publication span of the last seven years.